LEARNING IMPROVEMENT EFFORTS HIT THE BALL USING THE MODIFIED BAT BALL GAME FUEL STUDENT IN A CLASS VI MOJOSONGO III SD STATE SCHOOL YEAR 2012/2013 - DWI NURHADI, IBNU (Jurnal Phederal Penjas, 2013)
The purpose of this research is to improve learning outcomes using a modification of the ball hitting the bat in a game of fuel in class VI A Mojosongo III Elementary School Surakarta academic year 2012/2013.This research is a classroom action research (CAR). The experiment was conducted in two cycles, with each cycle consisting of planning, action, observation and reflection. Subjects were students of class VI A Mojosongo III Elementary School Surakarta academic year 2012/2013 amounted to 40 students consisting of 21 male students and 19 female students. Data sources are from teachers and students, learning outcomes data obtained through the ball hitting performance tests, observation sheet used to collect data on the students' activities following the process of learning to hit the ball using a modified bat. Data analysis techniques used in this research is descriptive quantitative analysis based on percentage techniques.The results of this study can be summarized as follows: Improved learning outcomes that include aspects of affective, cognitive and psychomotor of 40 students only 13 students who achieve KKM or 32.5% in the initial conditions, increased to 52.50% or 21 students who reach the limit completed by the end of the cycle I. Furthermore, increased to 80% or 32 students who reached the completion by the end of the second cycle. Thus, action research in class VI A Mojosongo III Surakarta Elementary School in an effort to improve learning outcomes using a modification of the ball hitting the bat has been successful in improving learning outcomes in students hit the ball.Conclusions This study is the use of Modifications Improve Learning Outcomes Bat Hitting Ball Game Ball In fuels By Grade VI Elementary School A Mojosongo III Surakarta academic year 2012/2013.Keywords: hit the ball, bat, quantitative analysis